Protein 3D Structure and Electron Microscopy Map Retrieval Using 3D‐SURFER2.0 and EM‐SURFER. Issue 1 (8th December 2017) - Han, Xusi; Wei, Qing; Kihara, Daisuke
Abstract: With the rapid growth in the number of solved protein structures stored in the Protein Data Bank (PDB) and the Electron Microscopy Data Bank (EMDB), it is essential to develop tools to perform real‐time structure similarity searches against the entire structure database. Since conventional structure alignment methods need to sample different orientations of proteins in the three‐dimensional space, they are time consuming and unsuitable for rapid, real‐time database searches. To this end, we have developed 3D‐SURFER and EM‐SURFER, which utilize 3D Zernike descriptors (3DZD) to conduct high‐throughput protein structure comparison, visualization, and analysis. Taking an atomic structure or an electron microscopy map of a protein or a protein complex as input, the 3DZD of a query protein is computed and compared with the 3DZD of all other proteins in PDB or EMDB. In addition, local geometrical characteristics of a query protein can be analyzed using VisGrid and LIGSITE CSC in 3D‐SURFER. This article describes how to use 3D‐SURFER and EM‐SURFER to carry out protein surface shape similarity searches, local geometric feature analysis, and interpretation of the search results. © 2017 by John Wiley & Sons, Inc.